Emphysematous Cystitis Occurred in the Case Treated with Steroid for Autoimmune Hepatitis - Tateki Yoshino; Shinya Ohara; Hiroyuki Moriyama (Case Reports in Urology)
Emphysematous cystitis is a rare clinically entity, more commonly seen in diabetic, immunocompromised patients, which was characterized by air within the bladder wall and lumen. A 83-year-old woman was introduced to our department with fever elevation and abnormal findings of computed tomography (CT). She took orally prednisolone for autoimmune hepatitis. Pelvic CT revealed diffuse air throughout the bladder wall. Urinalysis showed combined hematuria and pyuria. Escherichia coli was detected in blood culture. Abnormal findings of complete blood count and laboratory examination included an elevated WBC count (12,200/L), C-reactive protein (11.7 mg/dL), and creatinine (1.07 mg/dL). Cystoscopy confirmed diffuse submucosal emphysema throughout. On the basis of diagnosis with emphysematous cystitis, she was treated with antibiotics based on the results of blood culture and indwelling Foley catheter. After treatment, the improvement of inflammatory findings and submucosal emphysema on cystoscopy and CT were achieved.